1998
DOI: 10.1159/000006785
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Cholesterol Levels Predict High Perioperative Mortality in Patients Supported by a Left-Ventricular Assist System

Abstract: Background: Although the use of a left-ventricular assist system (LVAS) provides circulatory support for end-stage heart failure patients awaiting heart transplantation, this procedure is accompanied by a relatively high perioperative mortality. The aim of this retrospective study was to identify those patients preoperatively which have the highest perioperative mortality. Methods and Results: Forty-five consecutive patients undergoing LVAS implantation were evaluated for preoperative risk factors, including b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…Serum TG, LDL-C, HDL-C and apo B levels were lower in patients with IDC than the controls but these were also not statistically different. Our findings confirm the paradox that total cholesterol levels are decreased proportionally with the severity of HF (Richartz et al 1998;Vredevoe et al 1998;Rauchhaus et al 2000). This inverse relationship between mortality and lipid lipoprotein levels has been observed in other disease states and populations (Lowrie and Lew 1990;Gui et al 1996;Elliot and Wiles 1997;Fraunberger et al 2000).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Serum TG, LDL-C, HDL-C and apo B levels were lower in patients with IDC than the controls but these were also not statistically different. Our findings confirm the paradox that total cholesterol levels are decreased proportionally with the severity of HF (Richartz et al 1998;Vredevoe et al 1998;Rauchhaus et al 2000). This inverse relationship between mortality and lipid lipoprotein levels has been observed in other disease states and populations (Lowrie and Lew 1990;Gui et al 1996;Elliot and Wiles 1997;Fraunberger et al 2000).…”
Section: Discussionsupporting
confidence: 89%
“…It would be reasonable to expect that high cholesterol would be a risk factor and have deleterious effects on mortality in patients with established HF. However, preliminary reports have suggested that there is an increased mortality in HF patients with low cholesterol (Richartz et al 1998;Vredevoe et al 1998;Rauchhaus et al 2000).…”
Section: © 2005 Tohoku University Medical Pressmentioning
confidence: 99%
“…Several studies reported that patients with ischemic and nonischemic HF appear to have an opposite pattern (‘reverse epidemiology'), with low levels being associated with a worse prognosis independent of other prognostic factors [13,20]. Rauchhaus et al [16] studied 414 patients with HF and found a 36% decreased risk of mortality with each millimole per liter increase in total cholesterol, independent of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquinone (Q10), an essential product of cardiac mitochondrial respiration, is reduced in patients with congestive HF [14,15,16,17,20,26]. Treatment with statins was shown to reduce ubiquinone levels and could thus be potentially harmful [14,15,16,17,20].…”
Section: Discussionmentioning
confidence: 99%
“…В том же году опубликованы результаты исследова-ния, проведенного B.M. Richartz и соавт., где ретроспек-тивно оценивали прогностическую роль ОХ у пациентов с ХСН, которым была выполнена операция по поводу имплантации искусственного левого желудочка сердца (ИЛЖС) [5]. С этой целью пациентов, перенесших имплан-тацию ИЛЖС, разделили на 2 группы: пациенты, которым впоследствии успешно провели операцию по пересадке сердца (n = 25) и пациенты, которые умерли до транс-плантации сердца (n = 20).…”
Section: высокий уровень холестерина у пациентов с хсн  вопрос остаеunclassified